Application of Insecticides on Eggs of Callosobruchus chinensis L. Using Different Types of Pulse Seeds - Pramanik, MZA; Sardar, MA (Journal of Agriculture & Rural Development, 2008)
Experiments were carried out in the laboratory to assess the effectiveness of Nogos, Malathion, Sevin and Limper on lentil, gram, grasspea, greengram and blackgram seeds with eggs of pulse beetle, Callosobruchus chinensis L. Insecticides were sprayed on the seeds along with eggs and found that all the tested insecticides inhibited hatching of eggs resulting in significantly lowest rate of adult emergence. Nogos and Malathion recorded the lower number of emergent adults. The overall 26.35- 100% reduction of seed damage and 40-100% weight losses were achieved in insecticides treated seeds of five different types of pulses showing highest reduction in seed damage and weight losses due to Nogos and Malathion treatments. The treatment of the pulse seeds with the insecticides did not affect the seed germination. Key words: Insecticides, pulse beetle, egg treatment, pulses, seed damage.